2008
DOI: 10.1021/jp0761517
|View full text |Cite
|
Sign up to set email alerts
|

Pt(II) Uptake by Dendrimer Outer Pockets:  1. Solventless Ligand Exchange Reaction

Abstract: Density functional theory is used to elucidate molecular-level details of the complexation of Pt(II) metal compounds with PAMAM dendrimers. Particular attention is given to the ligand exchange reaction (LER). Binding of Pt(II) complexes to one dendrimer atom site (monodentate binding) is found to be thermodynamically feasible. Tertiary amine nitrogen (N3) is found to be the most favorable binding site in agreement with previous experimental work. Comparing the binding of Pt(II) species to atom sites in simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
(42 reference statements)
5
13
0
Order By: Relevance
“…The broad absorption peak of CPAMAM at 301 nm is converted to a narrow and strong peak at 292 nm after 24 h, which is consistent with the phenomenon of Pd 2+ complexes with the fourth-generation dendrimer in the aqueous phase . This change may result from ligand exchange, including chloride, the internal amine groups in CPAMAM, and water . The new strong peak at 292 nm is caused by ligand–metal charge transfer and is related to the formation of metal ion/hyperbranched polymer macromolecules. , …”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The broad absorption peak of CPAMAM at 301 nm is converted to a narrow and strong peak at 292 nm after 24 h, which is consistent with the phenomenon of Pd 2+ complexes with the fourth-generation dendrimer in the aqueous phase . This change may result from ligand exchange, including chloride, the internal amine groups in CPAMAM, and water . The new strong peak at 292 nm is caused by ligand–metal charge transfer and is related to the formation of metal ion/hyperbranched polymer macromolecules. , …”
Section: Resultssupporting
confidence: 73%
“…38 This change may result from ligand exchange, including chloride, the internal amine groups in CPAMAM, and water. 55 The new strong peak at 292 nm is caused by ligand−metal charge transfer and is related to the formation of metal ion/hyperbranched polymer macromolecules. 56,57 The addition of 10 equiv of NaBH 4 results in the reduction of CPAMAM (Pd 2+ ) to Pd@CPAMAM, and the solution turns dark brown (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the experimental work has been devoted to elucidate aspects of the ligand substitution reaction, also called ligand exchange reaction (LER). 4,7,8 Our previous study 9 on solventless ligand exchange reaction (LER) of tetrachloroplatinate anion and its mono-and diaquated species revealed that binding of Pt(II) to one dendrimer site (monodentate binding) is thermodynamically feasible in agreement with previous NMR experiments. 8 Notwithstanding the combined NCB (noncovalent binding) + LER free energy of PtCl 4 2to bind directly to a tertiary amine N (N3) site is greater than the NCB free energy of any other competitor ion, 9 its activation energy toward direct binding with the N3 site was found to be higher than its activation energy toward aquation.…”
Section: Introductionsupporting
confidence: 73%
“…Previously dendrimers have been examined sporadically as delivery vehicles for several different types of platinum drugs and complexes [15][16][17][18][19][20][21][22]. These dendrimers have included PAMAM, polyglycerol [22], poly(propyleneimine) [23], and thiol-yne derived [21] dendrimers with the active components of both cisplatin [17] and oxaliplatin [16] and a novel DNA intercalating platinum complex [15].…”
Section: Introductionmentioning
confidence: 99%